2009
DOI: 10.1007/s12016-009-8175-5
|View full text |Cite
|
Sign up to set email alerts
|

Mold and Human Health: Separating the Wheat from the Chaff

Abstract: The term "mold" is utilized to define the ubiquitous fungal species commonly found in household dust and observed as visible multicellular filaments. Several well-defined human diseases are known to be caused or exacerbated by mold or by exposure to their byproducts. Among these, a solid connection has been established with infections, allergic bronchopulmonary aspergillosis, allergic fungal rhinosinusitis, hypersensitivity pneumonitis, and asthma. In the past decades, other less-defined and generally false co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…These include Allergic Bronchopulmonary Mycosis (ABPM), Allergic Fungal Sinusitis (AFS) and Hypersensitivity Pneumonitis (HSP). 45 While exposure to fungi clearly can worsen each of these conditions, complete fungal avoidance has not been shown to result in clinical improvement. The goal of environmental control for these disorders therefore is to avoid making them worse.…”
Section: Other Hypersensitivity Disordersmentioning
confidence: 99%
“…These include Allergic Bronchopulmonary Mycosis (ABPM), Allergic Fungal Sinusitis (AFS) and Hypersensitivity Pneumonitis (HSP). 45 While exposure to fungi clearly can worsen each of these conditions, complete fungal avoidance has not been shown to result in clinical improvement. The goal of environmental control for these disorders therefore is to avoid making them worse.…”
Section: Other Hypersensitivity Disordersmentioning
confidence: 99%
“…Fungi cause hypersensitivity pneumonitis, asthma, aspergilloma, allergic bronchopulmonary aspergillosis, fungal sinusitis and constitutional symptoms like fatigue, nausea, cognitive dysfunction, immune dysfunction and toxic mold syndrome [5,6]. A meta-analysis showed that building dampness and molds are associated with 30-50% increase in respiratory and asthma related health outcomes [table/ Fig-2a,b]: Resolution of lesions seen in both lung fields, few areas of mosaic perfusion persists.…”
Section: Discussionmentioning
confidence: 99%
“…Wood and wood-based products, such as building materials, are subject to exposure to indoor fungi contaminated environments, causing sick-building syndrome (SBS) or toxic-mold syndrome (Bush et al 2006;Pettigrew et al 2010). With a broad range of pH and temperature values, fungi easily grow when the moisture content of wood exceeds 60% (Viitanen and Ritschkoff 1991).…”
Section: Introductionmentioning
confidence: 99%